Adventure Based Learning Experience (ABLE) - White, Robert M. (Journal of the American Academy of Special Education Professionals, 2007)
For the purpose of this research project an outdoor education program was developed for students (aged between 10-14) displaying signs of emotional difficulties in engaging with school and family life. The project investigated the effective use of an Integrated Adventure Based Educational program delivered in a complimentary milieu of classroom, outdoor and "wilderness" venues. Participants of the Adventure Based Learning Experience (ABLE) program reported positive change. In interview, 86% of the students reported that their self-confidence had improved, 95% reported feeling more comfortable at school, and 64% believed that they had become more aware of the needs of others. Furthermore, 88% say that they have an increased ability to regulate their emotions, and 75% say they have experienced more positive interactions with their family since participating in the program. Outdoor education proponents have argued that a systematic approach to experiential learning through challenge can develop participants trust, social competence and group cohesion. This study demonstrates significant gains in social competence for 22 Year 8 students participating in the ABLE program as compared to the control groups.